Nutritional status and morbidity profile of school going adolescent boys in an urban area - Rajderkar, Shekhar S.; Dudhabhate, Birappa T. (International Journal Of Community Medicine And Public Health, 2020)
Background: The aims and objectives of the study were to study the morbidity profile and nutritional status of study population and to study the risk factors associated with morbidity in study population. Methods: This cross-sectional study was conducted on boys studying in the municipal corporation school in Tasgaon, Sangli, Maharashtra. Total 450 adolescent boys (age between the 17 to 19 years) from class X, XI & XII and who were not seriously ill were included in the study. Results: Most common morbidity was pallor seen in 40% students followed by ENT related problems seen in 38% students, skin problems seen in 30% of the patients. 52% students were found to underweight. 88.44% students were having one or other type of symptoms and only 11.56% students were asymptomatic. Proportion of underweight students was same in both religions, both urban and rural students, in all types of families and in all economic classes. Proportion of symptomatic students was quite more in Hindu religion, more in students from urban areas and in students belonging to class I & II socio economic status. Conclusions: As more than half of the students were underweight, it was related to nutritional deficiencies because of lack of awareness regarding proper nutrition.